Pengaruh Kinerja Lingkungan, Ukuran Perusahaan, Leverage dan Sales Growth terhadap Pengungkapan Emisi Karbon - Suhardi, Mutiara Khairunnisa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Indonesian government has mandated corporate social and environmental responsibility reporting, shifting from its previous voluntary approach. However, many companies in Indonesia have yet to fully disclose their carbon emissions. This study examines the influence of environmental performance, firm size, leverage, and sales growth on carbon emission disclosure. Carbon disclosure is measured using a checklist from the Carbon Disclosure Project, which assesses accountability and strategic responses to climate change. The research analyzes 31 companies using panel data processed with Eviews 12 software. The findings show that firm size positively affects carbon emission disclosure, as larger companies with more resources tend to be more engaged in climate change mitigation efforts, leading to better disclosure practices. Conversely, leverage and sales growth negatively impact disclosure; firms with high debt levels often prioritize repayment over environmental reporting, while growing companies may focus more on financial performance than sustainability reporting. Additionally, the study finds that environmental performance, whether strong or weak, does not significantly affect carbon emission disclosure. These results suggest that while firm size facilitates disclosure, financial priorities and growth strategies can limit companies' willingness to report their carbon emissions transparently.